2021
DOI: 10.3390/ijgi10090597
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for Developing Predictive Spatial Models of Crime and New Methods for Measuring Their Accuracy

Abstract: A literature review of the important trends in predictive crime modeling and the existing measures of accuracy was undertaken. It highlighted the need for a robust, comprehensive and independent evaluation and the need to include complementary measures for a more complete assessment. We develop a new measure called the penalized predictive accuracy index (PPAI), propose the use of the expected utility function to combine multiple measures and the use of the average logarithmic score, which measures accuracy di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Relevant statistical metrics are summarized in White and Hunt (2022). Crime analysts should avoid solely using PAI, as it is not a reliable metric (Joshi et al 2021;Galvis, Hernández-Romero, and Gómez 2022). Instead, we suggest analysts use PEI and/or PEI* as outlined here and look for better metrics as they are developed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relevant statistical metrics are summarized in White and Hunt (2022). Crime analysts should avoid solely using PAI, as it is not a reliable metric (Joshi et al 2021;Galvis, Hernández-Romero, and Gómez 2022). Instead, we suggest analysts use PEI and/or PEI* as outlined here and look for better metrics as they are developed.…”
Section: Discussionmentioning
confidence: 99%
“…where measured PAI refers to calculating PAI over a single time period, and predictive PAI refers to evaluating PAI from two different time indices (Van Patten, McKledin-Coner, and Cox 2009). To address various study areas, one study developed the penalized predictive accuracy index (PPAI), where the area ratio is penalized (Joshi et al 2021). However, mathematicians have shown that PAI and its adaptions are still susceptible to artificial manipulation since PAI increases as subspace size (e.g., grid cell height, street length) decreases (Galvis, Hernández-Romero, and Gómez 2022).…”
Section: 𝑛′mentioning
confidence: 99%